Bacille Calmette-Guérin-specific IgG titres among infants born to mothers with active tuberculosis disease in Uganda - Diana Sitenda; Phillip Ssekamatte; Rose Nakavuma; Andrew Peter Kyazze; Felix Bongomin; Joseph Baruch Baluku; Rose Nabatanzi; Davis Kibirige; Robert J. Wilkinson; Annettee Nakimuli; Stephen Cose; Irene Andia-Biraro (BMC Immunology)
Abstract Background Infants born to mothers with active tuberculosis disease (ATB) are at risk of poor clinical outcomes such as low birth weight and perinatal mortality. However, little is known about the influence of maternal ATB exposure on their vaccine responses during infancy. The study explored how maternal ATB affects infants’ vaccine responses, hypothesising reduced responses to Bacille Calmette-Guérin (BCG) and other infant vaccines. Methods This was a case-control study with a longitudinal component of infants born to mothers with bacteriologically confirmed ATB (cases) and infants born to mothers without ATB (controls) carried out between September 2021 and June 2022. Quantitative BCG, diphtheria, tetanus, and measles-specific IgG ELISA assays were performed on infant plasma harvested from lithium-heparin blood collected on first encounter after birth (0), at 3, 6, and 9 months. We used prism v10.1.2, mixed-effects modelling, and Tukey’s multiple comparison testing to determine mean differences (MD) between the cases and controls at all time points. Results Exposed infant cases had reduced IgG titres to BCG at baseline compared to the controls (p = 0.032), with a mean of 125.8 vs. 141.1 IU/mL, respectively. This difference was, however, not sustained at the other time points. Similarly, we demonstrated trends towards reduced responses to tetanus, diphtheria, and measles vaccines among infant cases at baseline and three months. However, the trend was not sustained at months six and nine. The mean titres for tetanus at baseline and 3 months for cases versus controls are 1.744 vs. 2.917 IU/mL (p < 0.0001) and 1.716 vs. 2.344 IU/mL (p = 0.018), respectively. The mean titres for diphtheria at 3 months for cases versus controls were 0.022 vs. 0.075 IU/mL (p = 0.006), respectively. Conclusion We have demonstrated that maternal TB disease influences vaccine responses to BCG and other infant vaccines. This has implications for increased risk of childhood TB and other preventable diseases. Clinical trial number Not applicable.